Identification of Waste Handling Compliance of Sharp Objects at Universitas Gadjah Mada Academic Hospital Yogyakarta - Timuryani Nugraheni (Academic Hospital Journal, 2018)
Background: Health care processes that occur in the hospital cannot be separated from factor control and prevention of infection. One of the biggest challenges of the current hospital is to be able to reduce the number of infections that occur during the delivery of health services in progress.Objective: This research aimed to identify compliance with the infection control policy concerning health workers and sharp objects in order to prevent spread of infection and to decide upon the chain of infection transmission in Universitas Gadjah Mada Academic Hospital, Yogyakarta, Indonesia.Design:  This research was a descriptive analytic study. Data were collected by observation methods using a survey instrument in the form of a check list. The processing of data involved factor analysis and narratives in descriptive form with percentages and tables.The study population involved total sampling of 30 percent of the total measures undertaken by syringe healthcare workers who work in the ER, Intensive Care Installation, Operation Room and Midwifery Care Lounge. The sample set included 40 activities. The Observation Sheet was based on the Guide PPI from the 2011 Nurses Association of Infection Prevention and Control.Results: The incidence of needle stick during January - April 2015 increased significantly to 4 events. Rate of compliance officers in managing sharps waste was: 67.5% with 25 % of corporate compliance officers not doing recapping or closure of needles (minimum scale). A sharp object was not given to others as much as 82.5% (Medium scale). When intending to give a sharp object to another person then the container was used as much as 57.5% (minimum scale). Sharps waste were put into a special puncture resistant and waterproof box 97.5% (scale of Good). Safety box 3/4 full of sharps waste was sealed or sealed and thrown into the garbage storage area as much as 75% (minimum scale).Conclusions: The availability of adequate infrastructure, e.g. Safe Injecting SPO, SPO sharps waste management, availability of containers for storing syringe when it will be handed over to another officer, and the availability of adequate safety box needs to be improved. Workers should strictly follow the NSI (Needle Stick Injury) prevention and control program and execute compliance based on SPO guided by the universal precautions and hierarchical control policy.